The Da’wah Message in the Film "Tarung Sarung": Faith, Worship, and Moral Behavior - Choirin, Muhammad; Fajarulloh, Sulton; Guleng, Marlon Pontino (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
Movies are popular with all age groups, including teenagers. For this reason, movies are often used as a medium for conveying a religious message. Thus, movies are not only for entertainment but also have a function of religious education. The film "Tarung Sarung" by Archie Hekagery has taken on this role. The purpose of this qualitative study is to investigate the content of the sermon messages in the film "Tarung Sarung". Using Roland Barthes ' semiotic model, the analysis is based on words and sentences. The investigation revealed that there are three main messages of the sermon, namely the message of faith (akidah), worship (ibadah), and moral behaviour (akhlak). The message of faith is about conveying belief in Allah, sincerity (ikhlas) and peace (salam). As for the worship aspect, there are messages related to the hijab in accordance with Islamic law, prayer (sholat), the values of gratitude, and sincerity in worship. Finally, moral behaviour includes various messages of kindness, such as the teachings of filial piety toward parents, etiquette, and the law of just rent.